Contribution of Reading English Journals to Increase Academic Writing Skills for English Education Department Students of UPI YPTK Padang - Krisa Ardelia (Lesson Journal: Languange, Applied Linguistics, and Education Journal, 2020)
This research purposed to analyze the Contribution of Reading English Journals to Increase Academic Writing Skills for English Department Students of Putra Indonesia University "YPTK" Padang. This research is a qualitative research with document analysis type. Sampling data was collected using purposive sampling technique. The research sample consisted of 5 participants with a population of 22 participants. The research that researchers conducted is documents analysis of student academic writing assignments, which aims to determine the contribution of reading English journals specifically for English department students to improving academic writing skills. The instruments used in data collection were academic writing tasks of Paper Thesis Writing class. Data analysis used the form of quizzes by Arnold (2017). Based on the research that has been done, it is obtained assignment I <task II, 137 <197, with a total difference of 60 points. So that reading English journals in the Extensive reading class has an effect on increasing student work on the thesis writing scores for students of the English Department of the Putra Indonesia University "YPTK" Padang.